Principal Leadership Strategies to Improve Teacher Performance: A Case Study in Islamic Elementary - Desi Wulandari; Bambang Budi Wiyono; Sunarni Sunarni; Ali Imron (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study investigates the strategies employed by the principal of Islamic Elementary School Anak Saleh Malang, to improve teacher competence and their subsequent impact on educational outcomes. A case study design and a descriptive qualitative methodology were used, and semi-structured interviews, document analysis, and non-participant observations were used to gather data. The findings indicate that the principal employs a humanistic and familial leadership model, emphasizes individual motivation, mandates regular professional development, conducts systematic performance reviews, and encourages deliberate teaching strategies. These strategies have had a direct influence on improved student achievement as well as greater teacher professionalism. The study emphasizes how crucial leadership techniques based on organized development, motivation, and a reflective culture are to improving academic achievement. It suggests that to achieve long-term educational achievement, principals must foster professional development through efforts in strategic, consistent, and compassionate leadership.